An 'in‐cell trial' to assess the efficacy of a monovalent anti‐MET antibody as monotherapy and in association with standard cytotoxics. Issue 2 (18th December 2013) - Benvenuti, Silvia; Gentile, Alessandra; Lazzari, Luca; Arnesano, Addolorata; Trusolino, Livio; Comoglio, Paolo M.
Abstract : In clinical practice, targeted therapies are usually administered together with chemotherapeutics. However, little is known whether conventional cytotoxic agents enhance the efficacy of targeted compounds, and whether a possible synergy would be dictated by drug‐sensitizing genetic alterations. To explore these issues, we leveraged the design of clinical studies in humans to conduct a multi‐arm trial in an 'in‐cell' format. Using the MET oncogene as a model target and a panel of genetically characterized cell lines as a reference population, we found that two different chemotherapeutic regimens – cisplatin and 5‐fluorouracil – exerted widespread cytotoxic activity that was not further enhanced by MET inhibition with a monovalent anti‐MET antibody. From a complementary perspective, targeted MET inhibition was successful in a selected complement of cells harboring MET genomic lesions. In this latter setting, addition of chemotherapy did not provide a therapeutic advantage. Mechanistically, chemotherapeutics did not influence the basal activity of MET in cells with normal MET genomic status nor did they contribute to neutralize MET signals in cells with MET amplification. These data suggest that tumors displaying MET aberrations achieve plateau responses by MET monotherapy and do not receive further benefit by addition of cytotoxic treatments. Highlights: MET targeted therapy is effective per se when tumors exhibit MET amplification. MET targeted therapy outperforms standard cytotoxics in genetically defined patients. MET targeted therapy is dispensable in not MET‐addicted tumors.